The Prevalence of Toxoplasma Infection among Free-Ranging Chickens in Southern Iran Using IFA and Nested-PCR - Q Asgari; MH Motazedian; B Esmaeelzadeh; M Kalantari; GhR Hatam (Iranian Journal of Parasitology, 2009)
Background: As consumption of chicken meat may be as one of the sources of human infection, this study was undertaken to determine the prevalence of T. gondii in farm chickens (Gallus gallus domesticus) in Shiraz, southern Iran.